2020
DOI: 10.5430/wje.v10n4p130
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Attitudes Toward the Formal Integration of Facebook in Their Education: Investigation Guided by Rogers' Attributes of Innovation

Abstract: The aim of the study was to examine students’ attitudes toward the formal integration of Facebook in their education at Al- Hussein Bin Talal University and to examine the relationship between their attitudes and their perceptions of Facebook’s attributes. The investigation was guided by Rogers' (2003) attributes of innovation. A descriptive method was adopted in which a questionnaire was used to collect data from 99 undergraduate university students from the college of education. The results show that the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Relative advantage-has a direct and significant impact on OER adoption. Similar findings were achieved by (Wang and Wang, 2016) (Rhein, 2021) (Schuwer and Janssen, 2018) (Nazari et al, 2013) (Tanye, 2016), (Almohtadi and Aldarabah, 2021) and (Coleman-Prisco, 2017). In contradiction (Bond et al, 2021), (Colvard et al, 2018) and(Tlili et al, 2022) claimed that relative advantage had no effect on OER adoption, as faculty still believe that creating their own teaching/research materials save more time and effort than finding, modifying, and using OER.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Relative advantage-has a direct and significant impact on OER adoption. Similar findings were achieved by (Wang and Wang, 2016) (Rhein, 2021) (Schuwer and Janssen, 2018) (Nazari et al, 2013) (Tanye, 2016), (Almohtadi and Aldarabah, 2021) and (Coleman-Prisco, 2017). In contradiction (Bond et al, 2021), (Colvard et al, 2018) and(Tlili et al, 2022) claimed that relative advantage had no effect on OER adoption, as faculty still believe that creating their own teaching/research materials save more time and effort than finding, modifying, and using OER.…”
Section: Discussionsupporting
confidence: 74%
“…In the context of OER, DOI theory can lay out the factors formulating the adopter's perceptions of open resources in higher education (Essmiller, 2021) (Almohtadi and Aldarabah, 2021). Faculty's behavior and motivation against OER are subjective and embedded within community and institution context (Schuwer and Janssen, 2018).…”
Section: Diffusion Of Innovation Rogers' Theory (Doi)mentioning
confidence: 99%
“…It provided them with multi-functional and accessible varieties of interpersonal interests. This point is related to the study of Almohtadi and Aldarabah (2021), which suggests that students had positive and high attitudes toward Facebook in terms of its relative advantage, ease of use, compatibility, trialability, and observability. Similarly, Moghadam and Shamsi (2021) found that their participants rated Facebook as an appropriate teaching tool.…”
Section: Discussionmentioning
confidence: 92%